Efektivitas infusa buah jambu bol (Syzygium malaccense) sebagai antidiare pada mencit (Mus musculus) - Santosa, Alfian; Purnawarman, Trioso; Mustika, Aulia Andi; Rahma, Anisa; Sutardi, Lina Noviyanti (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2024)
Background: Malay rose apple (Syzygium malaccense) fruit has been used for a long time as a traditional medicine for diarrhea by the community. Malay rose apple fruit contains active compounds such as flavonoids, tannins, and terpenoids and could be used as an antidiarrheal drug. Objective: This study aims to test the effectiveness of the infusion of Malay rose apple fruit as an antidiarrheal agent in mice (Mus musculus). Methods: This research uses the method of intestinal protection and intestinal transit. The experimental animals in this study were 25 mice, which were divided into 5 groups, consisting of negative control (1% Tween 80), positive control group (loperamide HCl), and treatment groups using infusion of Malay rose apple fruit at concentrations of 50%, 75%, and 100%. The parameters assessed in the intestinal protection method are the frequency of defecation and the consistency of the stool, while the intestinal transit method is the ratio of marker passages. Results: The results showed that the antidiarrheal effect occurred at all concentrations. The best concentration as an antidiarrhea is shown by infusion with a concentration of 50%. The 50% concentration group had the smallest average on defecation frequency, stool consistency, and marker passage ratio compared to the values of the other treatment groups and was significantly different (P<0.05) compared to the value in the negative control. Conclusion: It can be concluded that the antidiarrheal effect of the infusion of Malay rose apple fruit occurs at all concentrations, with the best effect at a concentration of 50%.